Restricted Maximum Likelihood Estimators for Unbalanced of Oneway Repeated Measurements Model - Sarah Abbas Abdul-Zahra; Abdul Hussein Saber ALMouel (Genius Journals, 2023)
In this paper, we define and explain the one-way repeated measurements model for unbalanced data. Also next explore an alternative approaches to estimate the model's parameters and some of its properties.
Keywords: One-Way Repeated Measurements Model; Maximum Likelihood Method; Restricted Maximum Likelihood Method RMLM